Servant leadership and employee voice behavior: the role of employee work reflection and employee proactive personality - Xu, Zelei; Gu, Yu; Wang, Hongyu; Liu, Lili (Frontiers in Psychology, 2024)
Despite the recent proliferation of scholarly investigations on servant leadership, clarity remains elusive regarding the specific mechanisms and conditions underpinning employee cognitive processes and their responses to servant leadership.Drawing upon social cognitive theory, proposes a moderated mediation model tested through a time-lagged field data from 489 employees in Study 1 and an experimental data in Study 2. We found that servant leadership indirectly enhances employee voice behavior through increased employee work reflection. Additionally, we considered employee proactive personality as a boundary condition for the positive effect of servant leadership. Our results show that servant leadership prompts employee work reflection only when the level of employee proactive personality is high, which in turn increases employee voice behavior. This study presents significant theoretical and practical implications through the integration of social cognitive theory with servant leadership research.